A Case of Malignant Priapism Secondary to Muscle Invasive Bladder Cancer and Review of Palliative Management - David Fenton; Simon Han; Adrianna Lee; Alexandra Hernandez Perez; Kristina Gam; Jung Woo Kwon; Piyush Agarwal; Omer Raheem (Case Reports in Urology, 2025)
Malignant priapism secondary to a genitourinary malignancy is a rare and late-stage oncological finding. A 72-year-old man with a past medical history of muscle-invasive bladder cancer treated with trimodal therapy presented with altered mental status, white discharge from his Foley catheter, and bilateral corporal rigidity. Initial pelvic magnetic resonance imaging demonstrated engorgement of the corporal bodies without obvious tumor invasion. The patient eventually underwent penile exploration and bilateral decompression, and a biopsy revealed high-grade urothelial carcinoma invading the corporal tissues. Despite current guidelines for priapism, we present a three-tiered approach to the management of malignant priapism.